Mercury(II) extraction from solution with W/O type of liquid membrane emulsion using surfactant combination (span-80 + span-20) and 1-phenyl-3-methyl-4- benzoyl-5 -pyrazolone as carrier of cation - Hamzah, Baharuddin; Rahmawati, Sitti; Hardani, Ririen; Nurdin, Muhammad (International Journal of Engineering and Technology, 2018)
The study of mercury(II) solution was extracted by using W/O type liquid membrane emulsion combined of Span-80 & Span-20 surfactant and 1-phenyl-3-methyl-4-benzoyl-5-pyrazolone (HPMBP) as a cation carrier. The emulsion was prepared by mixing a 25 mL internal phase containing a nitric acid solution with a 25 mL membrane phase (surfactant and HPMBP solution in dodecane) then stirring at 2000 rpm emulsification speed for 8 min. Subsequently, the emulsion was mixed into the internal phase which containing mercury(II) solution and stirred at 299 rpm for 12 min. The optimum results show that the surfactant concentration was 2.5% with the emulsion volume and the external phase ratio of 1: 7 in pH condition of 3.Â In addition, the HPMBP concentration was used of 0.018 M with an internal phase concentration of 2.0 M nitric acid. Based on the results that the 50 mL liquid membrane emulsion could be extracting 30 ppm mercury (II) in 350 mL solution with the optimum extraction was 98.6%. This result is expected to be a reference for dealing with low concentrations of mercury waste in nature. Â Â